An iterative technique for the reconstruction of residual stress fields in a butt-welded plate from experimental measurement, and comparison with welding process simulation. (September 2019) - Chukkan, Jazeel Rahman; Wu, Guiyi; Fitzpatrick, Michael E.; Jones, Steve; Kelleher, Joe
Highlights: Residual stress mapping provides an efficient alternative to welding process simulations. Upper bound distributions of experimental data secure conservatism in integrity assessments. Internal equilibrium in the FE model play important role in residual stress mapping. Abstract: Residual stress is a factor which potentially affects the integrity of welded components. We have developed a methodology of assessment to establish the state of residual stress in a butt-welded plate by using a limited set of experimental measurements obtained using neutron diffraction. The unique longitudinal and transverse residual stress components, as a result of the welding process, are measured across the weld in three depths through the thickness. The measured residual stresses are then used to estimate a stress distribution for each stress component. The estimated stress distribution is then mapped to a finite element model of the weld plate, before adopting an iterative solution to reconstruct the residual stress fields. In addition, a traditional welding simulation is performed using the same weld plate details to predict and compare the residual stress distributions. It is shown that accurate residual stress field reconstruction is possible in and around the area of measurement using the limited measurement data from the neutron diffraction technique. In the estimated stress profiles, an upper-bound distribution is implemented in the weld and Heat Affected Zone (HAZ). This increases the efficiency and reduces the complexity of modelling. In the meantime, conservatism in the estimated stress is secured.